Magmatismo do batólito rapakivi Rio Branco, sw do Cráton Amazônico (MT) - de Araújo, Larissa Marques Barbosa; Godoy, Antonio Misson [UNESP] (My University, 2011)
Rio Branco Rapakivi Batholith is located on the southwestern portion of the Amazonian Craton in Mato Grosso and belongs to the Cachoeirinha Tectonic Domain, part of the Rio Negro-Juruena Geochronological Province, Central Brasil. The batholith is constituted by microgabbros to quartz microgabbros and microdiorites to quartz microdiorites, middle to fine-grained equigranular to porphyritic varieties form the Rio Branco Intrusive Basic Suite, showing a discontinuous distribution and located near the margins of the intrusion.Majorly constituted by porphyritic, granophyric and isotropic facies of Rio Branco Intrusive Acid Suit which is composed by older dark red rapakivi monzogranites to quartz monzonites and quartz sienites (1403±0.6 Ma) and the younger red rapakivi leuco-monzogranites (1382±49 Ma) and late equigranular to pegmatitic monzogranites. The magmatism is constituted by two distinct magmas related to the end of the collisional event of Cachoeirinha Orogeny, one with alkaline basalts generated in an intraplate environment and the other postorogenic to anorogenic with peraluminous to metaluminous compositions and define a high-K calc-alkaline to shoshonitic magmatism in transition among the I- and A-types. The contacts are marked by extensive mafic sills and dikes of alkaline basalts derived from intraplate environment of the Salto do Céu Intrusive Basic Suite (±808 Ma) associate to the Sunsás-Aguapei Orogenic Belt and metasedimentary rocks of the Aguapeí Grup.

O Batólito Rapakivi Rio Branco ocorre na porção sudoeste do Cráton Amazônico no estado do Mato Grosso, inserido no Domínio Tectônico Cachoeirinha, parte da Província Geocronológica Rio Negro-Juruena. O batólito é constituído por microgabros a quartzo micrograbros e microdioritos a quartzo microdioritos equigranulares finos a médios a porfiríticos da Suíte Básica Intrusiva Rio Branco, com uma distribuição descontínua e localizada nas bordas da intrusão ácida. Dominantemente ocorrem as fácies porfiríticas, granofíricas e isotrópicas da Suíte Ácida Intrusiva Rio Branco composta, a mais antiga por monzogranitos a quartzo monzonitos e quartzo sienitos vermelhos escuros rapakivi (1403±0.6 Ma) e a mais jovem e principal, por leuco-monzogranitos vermelhos rapakivis (1382±49 Ma), além das fácies tardias de monzogranitos equi-inequigranulares a pegmatóides. O magmatismo é definido dois magmas distintos relacionados ao evento colisional da Orogenia Cachoeirinha, um formado por basaltos alcalinos de ambiente intraplaca e o outro, por granitos peraluminoso a metaluminoso cálcio-alcalino de alto potássio a shoshonítico, de transição entre os tipos I e A, pós-orogênico a anorogênico. Os contatos externos ocorrem com extensas soleiras e diques de basaltos alcalinos formado em ambiente intraplaca da Suíte Básica Intrusiva Salto do Céu de (±808 Ma) associados à Orogenia Sunsás-Aguapeí ou com as rochas metassedimentares do Grupo Aguapeí. Palavras-chave: Cráton Amazônico, Batólito Rapakivi Rio Branco, geocronologia.
Rio Branco rapakivi batholith magmatism, Southwestern of Amazonian Craton - MT
Keywords: Amazonian Craton; Geochronology; Rio Branco Batolith Rapakivi; alkalinity; basalt; batholith; geochronology; isotopic analysis; magmatism; monzonite; quartz; Brazil; Mato Grosso